2017
DOI: 10.3847/1538-4357/aa6e53
|View full text |Cite
|
Sign up to set email alerts
|

The O2 A-Band in the Fluxes and Polarization of Starlight Reflected by Earth-Like Exoplanets

Abstract: Earth-like, potentially habitable exoplanets are prime targets in the search for extraterrestrial life. Information about their atmospheres and surfaces can be derived by analyzing thelight of the parent star reflected by the planet. We investigate the influence of the surface albedo A s , the optical thickness b cloud ,thealtitude of water clouds, and the mixing ratio of biosignature O 2 on the strength of the O 2 A-band (around 760 nm) in theflux and polarization spectra of starlight reflected by Earth-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 75 publications
2
36
0
Order By: Relevance
“…Additionally, linear line polarization could be introduced into the transmission spectrum by coherent scattering at electrons in the Earth's ionosphere, just like the Hanleeffect on the Sun, and then adds to the total polarization signal. Fauchez et al (2017) showed that gaseous absorption bands like the O 2 bands not only show up in flux spectra of light reflected by (exo)planets but also appear in polarization spectra. However, our QUV data do not show any polarization above 0.2-0.4%.…”
Section: Searching For Continuum and Line Polarizationmentioning
confidence: 99%
“…Additionally, linear line polarization could be introduced into the transmission spectrum by coherent scattering at electrons in the Earth's ionosphere, just like the Hanleeffect on the Sun, and then adds to the total polarization signal. Fauchez et al (2017) showed that gaseous absorption bands like the O 2 bands not only show up in flux spectra of light reflected by (exo)planets but also appear in polarization spectra. However, our QUV data do not show any polarization above 0.2-0.4%.…”
Section: Searching For Continuum and Line Polarizationmentioning
confidence: 99%
“…The new observational contribution in this work, however, is the large variation of this line independent of phase and not directly correlated to "A" or "P" sceneries. Fauchez et al (2017) investigate the influence of the planet surface albedo, cloud optical thickness, altitude of the cloud deck and the O 2 mixing ratio on the polarization in the O 2 -A band, and find that these parameters may not be easily discriminated in the higher optical depth regimes that can be probed with high spectral resolution. The cloud deck altitude and horizontal distribution across the region of the Earth that contributes strongest to the observed signal may be decisive factors for the appearance of the band, but more detailed simulations of Earth polarization measurements are needed to confirm this.…”
Section: O 2 -A Band Strengthmentioning
confidence: 99%
“…An example of the variability computed using PyMieDAP can be found in Rossi & Stam (2017) where it was used to generate the disk-integrated signals of Earth-like exoplanets with varying types and amount of coverage by liquid water clouds. Thanks to the use of Fourier coefficients, only a limited number of model computations were necessary: clear sky and cloudy case with different cloud-top altitudes.…”
Section: Horizontally Inhomogeneous Planetsmentioning
confidence: 99%
“…Firstly, because light is fully described by a vector and scattering processes by matrices, ignoring polarization can induce errors up to several percent in computed total fluxes both locally and disk-integrated (Mishchenko et al 1994;. In particular, in gaseous absorption bands, where the linear polarization usually differs from the polarization in the continuum (Fauchez et al 2017;Boesche et al 2009;Stammes et al 1994;Aben et al 1997), such errors will lead to errors in derived gas mixing ratios and e.g. cloud top altitudes .…”
Section: Introductionmentioning
confidence: 99%